When a little means a lot – slight daily cleaning is crucial for obligatory ant-tended aphids. Issue 1 (2nd January 2016) - Durak, R.; Węgrzyn, E.; Leniowski, K.
Abstract : Ant-aphid mutualism has been investigated by many authors but it is unknown if anti-predator protection provided by ants is the main benefit for aphids. The aim of our paper is to analyse the ant-aphid interactions in the absence of predators. Based on video recordings we distinguish ant behaviours in interactions with attended aphids and we present ant time-budget at different times of the day. We also test if an aphid colony can survive without ant attendance in an environment free from predators and we inquire how much ant attendance is needed to maintain an aphid colony in good condition. Our study shows that, despite the lack of predation pressure, aphids of the species Cinara tujafilina were not able to survive without ant attendance and the extinction was caused by the excessive honeydew that covered aphids and their surroundings. We also found that ants cleaning aphids was the most frequent and time-consuming activity in ant-aphid interactions. However, in general, ants interacted with aphids only for less than 5% of their total time-budget. Thus, despite the fact that cleaning seems to be crucial in aphid survival, surprisingly little ant effort is needed to maintain an aphid colony in good condition.